The Effect Of Human Trafficking And People Stuffing On Indonesian Migrant Workers - Hana Fortuna; Kirana Shasa Sahila; Muhammad Rizky Novianto (LEGAL BRIEF, 2022)
Indonesia is a country that sends many of its citizens to become a worker in other countries. Indonesian Citizens working abroad are referred to as Indonesian Migrant Workers. Indonesian Migrant Workers are Indonesian citizens who decide to work abroad through a selection with the Indonesian Migrant Workers Protection Agency or BP2MI for a certain period. However, in the process of recruitment to work, Indonesian Migrant Workers are overshadowed by the threat of becoming victims of human trafficking or human smuggling. The Crime of Trafficking in Persons and Human Smuggling is a transnational organized crime committed by an individual or group and moves regardless of the territorial boundaries and jurisdiction of another country. In its prevention and countermeasures, the government has an important role to be able to help Indonesian Migrant Workers to be able to participate in recruitment and do their jobs well without hesitation and fear of the threat of becoming victims of transnational organized crime. The role that Indonesian Government performed is to create laws and regulations governing transnational organized crime and its derivatives and integrate between relevant institutions and/or agencies that prevent, regulate and enforce laws and regulations that have been made regarding to the transnational organized crime and its derivatives to guarantee and protect Indonesian Migrant Workers from the threat of such crimes.